THE RESIDUE OF MILITARY REGIME DURING THE EARLY DEMOCRATIZATION ERA IN INDONESIA AND MYANMAR - Anugrah, Insan Praditya (CIC Lembaga Riset dan Konsultan Sosial, 2019)
This paper is a comparison of democracy structure between two Southeast Asian Nations, Indonesia and Myanmar during their early periods of Post-Praetorianism era where the state was controlled and dominated by the military. This paper found that In Indonesia, democratization after reformasi era in 1998 had successfully changed the structure of power, where the military determination in politics had been decline significantly, despite the military still hold the power to influence political and economic affairs. In Myanmar, the democratization was a result of long term transition previously planned by the military regime, so even in 2010 democratic election, the military still hold the control over the politics and tend to preserve their power within the new face of democratic system.